2017
DOI: 10.1111/tra.12528
|View full text |Cite
|
Sign up to set email alerts
|

Phosphatidylinositol (4, 5)‐bisphosphate targets double C2 domain protein B to the plasma membrane

Abstract: DOC2B is a high-affinity Ca2+ sensor that translocates from the cytosol to the plasma membrane (PM) and promotes vesicle priming and fusion. However, the molecular mechanism underlying its translocation and targeting to the PM in living cells is not completely understood. DOC2B interacts in vitro with the PM components phosphatidylserine, phosphatidylinositol (4,5)-bisphosphate [PI(4,5)P2] and target SNAREs (t-SNAREs). Here we show that PI(4,5)P2 hydrolysis at the PM of living cells abolishes DOC2B translocati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
17
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 70 publications
(141 reference statements)
2
17
0
Order By: Relevance
“…Vesicle fusion promotes the integration of GLUT4 into the PM, which facilitates glucose uptake. Several reports show that DOC2B is a soluble protein and can exist in the cytosol, consistent with DOC2B having no transmembrane domain [4,18,19]. DOC2B is speculated to regulate insulin-stimulated GLUT4 translocation via insulininduced DOC2B translocation from the cytosol to the PM, where the target-associated SNARE (t-SNARE) proteins reside [4,18,20,21].…”
Section: Introductionmentioning
confidence: 85%
See 1 more Smart Citation
“…Vesicle fusion promotes the integration of GLUT4 into the PM, which facilitates glucose uptake. Several reports show that DOC2B is a soluble protein and can exist in the cytosol, consistent with DOC2B having no transmembrane domain [4,18,19]. DOC2B is speculated to regulate insulin-stimulated GLUT4 translocation via insulininduced DOC2B translocation from the cytosol to the PM, where the target-associated SNARE (t-SNARE) proteins reside [4,18,20,21].…”
Section: Introductionmentioning
confidence: 85%
“…Several reports show that DOC2B is a soluble protein and can exist in the cytosol, consistent with DOC2B having no transmembrane domain [4,18,19]. DOC2B is speculated to regulate insulin-stimulated GLUT4 translocation via insulininduced DOC2B translocation from the cytosol to the PM, where the target-associated SNARE (t-SNARE) proteins reside [4,18,20,21]. At the PM, insulin stimulation increases DOC2B binding to phosphorylated syntaxin binding protein (STXBP)3, increasing SNARE complex formation [9,11,22].…”
Section: Introductionmentioning
confidence: 88%
“…These results agree with quantitative thermodynamic studies [64], which observed the Ca 2+ -induced membrane penetration experimentally. Notably, a similar configuration for the attachment of the C2B module to PIP2 was demonstrated for the Syt1 analog DOC2B [67], suggesting a general mechanism for the membrane anchoring of C2B domains.…”
Section: Discussionmentioning
confidence: 55%
“…In cell-free assays, Doc2b interacts with the SNARE complex to promote fusion of SNARE-liposomes (Groffen et al, 2010; Yao et al, 2011). Doc2b C 2 domains bind to phosphatidylserine-containing membranes in a Ca 2+ -dependent manner (Groffen et al, 2010) but also to PI(4,5)P 2 , a phospholipid enriched on the cytoplasmic leaflet of the plasma membrane (Michaeli et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…However, alteration of this interaction by mutations in the MID domain have no effect on Ca 2+ -induced Doc2b migration to the membrane (Groffen et al, 2004; Gaffaney et al, 2014). The presence of PI(4,5)P 2 targets Doc2b to the plasma membrane upon [Ca 2+ ] i elevation (Michaeli et al, 2017). Hence, Doc2b could support exocytosis by both of several mechanisms: i) together with Munc-13 for vesicle priming or superpriming; ii) Ca 2+ -dependently by enhancing membrane fusion.…”
Section: Introductionmentioning
confidence: 99%